2014
DOI: 10.1093/nar/gku539
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation with polyamines enhances the antibacterial and anticancer activity of chloramphenicol

Abstract: Chloramphenicol (CAM) is a broad-spectrum antibiotic, limited to occasional only use in developed countries because of its potential toxicity. To explore the influence of polyamines on the uptake and activity of CAM into cells, a series of polyamine–CAM conjugates were synthesized. Both polyamine architecture and the position of CAM-scaffold substitution were crucial in augmenting the antibacterial and anticancer potency of the synthesized conjugates. Compounds 4 and 5, prepared by replacement of dichloro-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 65 publications
3
54
0
Order By: Relevance
“…1). This observation is in accord with two conformers of clindamycin observed in crystal structures [2123] and docking studies [25], suggesting that there is room for clindamycin to rotate its pyrrolidynyl propyl group even once bound in the ribosome. …”
Section: Resultssupporting
confidence: 88%
“…1). This observation is in accord with two conformers of clindamycin observed in crystal structures [2123] and docking studies [25], suggesting that there is room for clindamycin to rotate its pyrrolidynyl propyl group even once bound in the ribosome. …”
Section: Resultssupporting
confidence: 88%
“…The presence of polyamine based skeleton in our molecules can attribute to the disruption of biofilm (Kostopoulou et al . ). The reaction of 3‐amino‐4‐aminoximidofurazan with the substituted nitriles yielded a small library of compounds with polyamine skeleton.…”
Section: Resultsmentioning
confidence: 97%
“…Another report also revealed that polyamine conjugated chloramphenicol showed higher antimicrobial property than the unconjugated chloramphenicol (Kostopoulou et al . ). So, we hypothesized that the polyamine based new synthetic molecules could be efficient antimicrobials.…”
Section: Introductionmentioning
confidence: 97%
“…As the structure of mammalian mitochondria is similar to prokaryotes [13, 14, 20], mitochondrial protein synthesis can also be inhibited by chloramphenicol. Our results indicate that chloramphenicol sharply suppresses ATP levels in human MM cell lines and primary MM cells at concentrations ≥ 25 μg/mL and significantly inhibits tumor growth at concentrations ≥ 50 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports showed that chloramphenicol inhibits mammalian mitochondrial protein synthesis and causes mitochondrial stress, leading to decreased ATP biosynthesis [914]. The use of chloramphenicol as an antimicrobial agent to treat bacterial infections has decreased over the years because it suppresses bone marrow function in humans secondary to inhibition of mitochondrial protein synthesis [15, 16].…”
Section: Introductionmentioning
confidence: 99%